Factors influencing the reduction of U(VI) by magnetite. (September 2020) - Ma, Yue; Cheng, Xi; Kang, Mingliang; Yang, Guangze; Yin, Meiling; Wang, Jin; Gang, Song
Abstract: Under suboxic and anoxic environments, magnetite is one corrosion product of iron being used in nuclear waste canisters. Previous studies have reported a complete reduction of U(VI) on the surfaces of biogenic and natural magnetite crystals, while incomplete reductions to U(V)/U(IV)-containing species have been observed on chemosynthetic magnetite. To date, the reasons behind such disparities remain poorly studied. This study shows that uranyl nitrate or uranyl acetate is mainly reduced to UO2+x oxides (e.g., U4 O9, U3 O8, etc.) by chemosynthetic magnetite under acidic conditions. When extra zero valent-iron was added, the reaction rate was significantly increased, and an improved but still incomplete U(VI) reduction was observed. Nitrate and ferric ions are ubiquitous in natural environment. Results demonstrate that the nitrate ion associated with uranyl and the ferric ion contained in magnetite or generated from U(VI) reduction have a non-negligible oxidative effect on the final products, which could mainly account for the incomplete reduction of U(VI) by chemosynthetic magnetite in the absence or presence of extra zero valent-iron observed in this study. Furthermore, the surface loading of uranium in U–Fe systems can, in part, unravel the discrepancies in various observations. An enhanced understanding of the U–Fe reaction mechanism can facilitate predictions of the extent of uranium mobility with respect to nuclear waste disposal and radioactive decontamination. Highlights: Uranyl is incompletely reduced to UO2+x oxides by chemosynthetic magnetite. Zero-valent iron can improve the reduction of U(VI) by magnetite. NO3 − associated with uranyl as well as Fe 3+ contained in magnetite or generated during U(VI) reduction can retard the reduction process.